Direct automated MALDI mass spectrometry analysis of cellular transporter function: inhibition of OATP2B1 uptake by 294 drugs - Unger, Melissa; Schumacher, Lena; Enzlein, Thomas; Weigt, David; Zamek-Gliszczynski, Maciej J.; Schwab, Matthias; Nies, Anne; Drewes, Gerard; Schulz, Sandra; Reinhard, Friedrich B. M.; Hopf, Carsten (Analytical chemistry, 2020)
OATP2B1, a member of the solute carrier (SLC) transporter family, is an important mechanism of substrate drug uptake in the intestine and liver and therefore a determinant of clinical pharmacokinetics and site of drug-drug interactions. Other SLC transporters have emerged as pharmacology targets. Studies of SLC transporter uptake to-date relied on radioisotope- or fluorescence-labeled reagents or low-throughput quantification of unlabeled compounds in cell lysate. In this study, we developed a cell-based MALDI MS workflow for investigation of OATP2B1 cellular uptake by optimizing the substrate, matrix, matrix-analyte ratio, and matrix application and normalization method. This workflow was automated and applied to characterize substrate transport kinetics and to test 294 top-marketed drugs for OATP2B1 inhibition and quantify inhibitory potencies necessary for extrapolation of clinical drug-drug interaction potential. Intra-assay reproducibility of this MALDI MS method was high (CV < 10%), and results agreed well (83% overlap) with previously published radioisotope assay data. Our results indicate that fast and robust MALDI MS cellular assays could emerge as a high-throughput label-free alternative for direct assessment of drug transporter function in DDIs and toxicities as well as enable drug discovery for transporters as pharmacology targets.
Gesehen am 22.12.2025